Level of knowledge, attitude and practice of testicular cancer and testicular self-examination among male students in a Centre for Foundation Studies in Pahang state of Malaysia students - Razak, Nor Fasihah; Ahmad Latif, Nur Afifah Natasha; Ahmad, Azmir (IIUM Press, 2025)
Background: The occurrence of testicular cancer among the young adult population has gradually increased throughout the decades. Although the incidence is increasing, the susceptible population shows lack of awareness that early detection of testicular cancer can reduce mortality risk. Testicular self-examination is a simple, convenient, and safe procedure that is essential for early detection of testicular cancer. Globally, the practice of testicular self-examination among young adults is unsatisfying. Thus, this study aimed to assess the level of knowledge, attitude and practice regarding testicular cancer and testicular self-examination among male students in a foundation centre, and to identify their associations with sociodemographic characteristics. Methods: A cross-sectional study was conducted among 386 eligible respondents who were recruited using stratified random sampling. A self-administered questionnaire was used to collect the knowledge, attitude and practice data on testicular cancer and testicular self-examination. The descriptive data were presented in frequency and percentage. The associations between the variables were analyzed using the Chi-square test. Results: Majority of respondents have poor knowledge (59.6%), favorable attitude (52.8%) and not practicing testicular self-examination (80.3%). The Chi-Square analysis showed a significant association between attitude with Kulliyyah and sources of information, as well as practice with Kulliyyah (p<0.05). Conclusion: The study found an unsatisfactory level of knowledge and practice on testicular cancer and testicular self-examination, although most of them have favorable attitude towards testicular cancer and testicular self-examination. Significant associations were found between the sociodemographic and attitude, as well as practice